Project-Based Learning as a Tool to Meet Learning Results: A Case Study of Teaching Microcontrollers - Camargo L., Julián R.; Flórez C., Oscar D.; Jutinico, Andres L. (International Journal of Online and Biomedical Engineering (iJOE), 2023)
This article presents a proposal of project-based learning (PBL) as a didactic tool to meet the learning results (LR) proposed in the syllabus of the course Digital Design with Microcontrollers taught in the Electronic Engineering course of the Faculty of Engineering of the Universidad Distrital Francisco José de Caldas in Bogotá, Colombia. Students are provided with all the information related to the project, the design methodology, what is expected from the project, and how to evaluate the results of the work done. The proposed methodology shows the students that, from a practical project usually applied to the real environment, the theoretical information shown in the classroom is immediately applicable, increasing their motivation and willingness to work. In addition, another skill, teamwork, is reinforced by applying this type of teaching, since each member of the working group (three students per group) has a role in the project’s development. The low-cost development kit CY8CKIT-059 for PSoC5LP, manufactured by Infineon Technologies AG, is used in the course to apply the proposal. As a case study to demonstrate the methodology, the design of a data logger that stores humidity and temperature from a digital sensor, developed as one of several projects presented by students in recent semesters, is presented. When comparing the quantitative results obtained from the course in previous semesters with those obtained after applying the project-based learning methodology, a significant improvement can be seen: the percentage of students passing is significantly higher.